Playing football in Cameroon as a girl: a match for equality - Bertho, B.; Grange-Omokaro, F.; Douna, I. M.; Malatesta, D. (Soccer & Society, 2024)
Football, whether played competitively or as a leisure-time activity, is a veritable social institution in Africa, that commands a strong physical and symbolic presence. It gives shape to social bonds and occupies a special place in the public`s imagination - globalized modernity, success - that is highly valued, in particular because of the great international careers of some African players. It thus creates opportunities for experiences that involve a political dimension: in the realm of football, social and cultural norms can be negotiated, and economic as well as cognitive resources circulate. Using ethnographic data gathered in the context of a study under way in Cameroon, we examine the ways in which girls gain access to the practice of football through a range of practices and strategies within a context characterized by multiple constraints.